Analisis Pemanfaatan Internet Sebagai Salah Satu Sumber Belajar Mahasiswa Program Studi Pendidikan Ekonomi Universitas Muhammadiyah Maumere - Aisah Sulaiman; Nur Chotimah; Rusli Hereng (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the benefits of the internet as a learning resource for students in the Economics Education Study Program at Mahammadiyah University Maumere. This study uses a descriptive method with a qualitative approach. This study provides an accurate description and explanation of the conditions or phenomena encountered. Data collection techniques include observation, interviews, documentation, and triangulation. The research subjects are 12 students from the 2021 cohort of the Economics Education Program. The utilization of the internet as a learning resource for students in the Economics Education Program at Muhammadiyah University of Maumere plays a significant role because the internet provides easy and quick access to various information such as learning materials, scientific journals, e-books, educational videos, and relevant and supportive resources. This enables students to access the latest information and a variety of up-to-date topics. The research findings indicate that economics education students at Muhammadiyah University of Maumere actively utilize the internet to search for references, access e-books, journals, educational videos, and participate in online discussions. The use of platforms such as Google, YouTube, TikTok, and AI tools like ChatGPT aids in understanding course materials. Despite network challenges, students seek solutions by relocating or using the campus network. They tend to choose reliable learning sources, reflecting strong digital literacy skills. Overall, the use of the internet enhances students' motivation and academic performance, leading to improved outcomes